2002
DOI: 10.1359/jbmr.2002.17.6.1034
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Acts as a Growth Factor on the Chondrocytes of Skeletal Growth Centers

Abstract: Childhood obesity frequently is associated with an increase in height velocity and acceleration of epiphyseal growth plate maturation despite low levels of serum growth hormone (GH). In addition, obesity is associated with higher circulating levels of leptin, a 16-kDa protein that is secreted from the adipocytes. In this study, we evaluated the direct effect of leptin on the chondrocyte population of the skeletal growth centers in the mouse mandibular condyle, a model of endochondral ossification. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
1
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(175 citation statements)
references
References 47 publications
9
158
1
7
Order By: Relevance
“…Intraarticular administration of leptin induced expression of IGF-1 and TGF␤ in rat chondrocytes at both the mRNA and protein levels. This stimulating effect may explain the enhanced proteoglycan synthesis observed in leptininjected rats, which may be further increased by the up-regulation of growth factor receptors, as was previously shown for IGF-1 receptor in leptin-stimulated mandibular condyles (45).…”
Section: Key Role Of Leptin In Oa 3125supporting
confidence: 59%
“…Intraarticular administration of leptin induced expression of IGF-1 and TGF␤ in rat chondrocytes at both the mRNA and protein levels. This stimulating effect may explain the enhanced proteoglycan synthesis observed in leptininjected rats, which may be further increased by the up-regulation of growth factor receptors, as was previously shown for IGF-1 receptor in leptin-stimulated mandibular condyles (45).…”
Section: Key Role Of Leptin In Oa 3125supporting
confidence: 59%
“…Both groups have found a negative calcium balance caused by renal calcium leak in such diabetic patients. Also, since leptin resistance is a feature of type-2 diabetes and several labs have indicated that leptin may be involved in the process of bone formation (Maor et al 2002, Tamasi et al 2003, a skeletal role for leptin in type-2 diabetes is a possibility. Two opposing mechanisms have been suggested: (1) leptin may work locally to promote osteoblastogenesis, and (2) leptin may work through a central hypothalamic relay to produce an osteoblastic inhibitory factor (Ducy et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Antisense and sense probes for in situ hybridisation were produced by transcription using an RNA labelling kit (Sp6/T7 digoxigenin [DIG]-RNA; Boehringer, Mannheim, Germany) following the company's instructions. The transduced and untransduced hepatocytes were hybridised with sense and anti-sense DIG-labelled RNA probes as described [37]. Hybrids were detected using anti-DIG antibodies conjugated with rhodamine (Cat.…”
Section: Methodsmentioning
confidence: 99%